IMPLEMENTASI MEDIA VIDEO ANIMASI DALAM PEMBELAJARAN IPA: STUDI DESKRIPTIF DI SMP IT AL-MUTTAQIEN MANISLOR - Indah Putri Nanda Sari; Diana Hasna Amatullah; Saepul Bahri; Wahyu Tresno; Novia Agustin; Endang Sukasih; Edward Alfin (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
Abstract The low student engagement and learning outcomes in science (IPA) require innovative and more interactive learning media. This study aims to describe the implementation of animated video media in science learning, analyze student responses, and identify challenges faced by teachers at SMP IT Al-Muttaqien Manislor. This research employed a descriptive qualitative approach involving a science teacher and 32 students of class VIII A. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The results show that animated video media was integrated into the Discovery Learning model in abstract science topics, particularly the organ systems. The use of animated videos made the learning materials easier to understand and increased student engagement. Students showed highly positive responses, indicated by improved learning focus, more active group discussions, and increased willingness to ask questions, along with improvements in cognitive, affective, and behavioral engagement during learning. Several challenges were identified, including limited technological facilities, technical disruptions, and suboptimal time management in classroom instruction. Overall, animated video media was effective in improving the quality of science learning by making the learning process more interactive and meaningful, although it still requires adequate infrastructure support and effective classroom management from teachers. Abstrak Rendahnya keaktifan dan hasil belajar IPA mendorong perlunya inovasi media pembelajaran yang lebih interaktif. Penelitian ini bertujuan mendeskripsikan implementasi media video animasi dalam pembelajaran IPA, respons siswa, serta kendala yang dihadapi guru di SMP IT Al-Muttaqien Manislor. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan subjek guru IPA dan siswa kelas VIII A sebanyak 32 orang. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model Miles, Huberman, dan Saldaña melalui reduksi data, penyajian data, dan penarikan kesimpulan, serta diuji keabsahannya melalui triangulasi dan member check. Hasil penelitian menunjukkan bahwa video animasi terintegrasi dalam model Discovery Learning pada materi IPA abstrak, khususnya sistem organ. Media ini membuat materi lebih mudah dipahami dan meningkatkan keterlibatan siswa. Respons siswa sangat positif, ditandai dengan meningkatnya fokus belajar, keaktifan diskusi, dan keberanian bertanya, serta peningkatan keterlibatan pada aspek kognitif, afektif, dan perilaku. Kendala yang ditemukan meliputi keterbatasan fasilitas, gangguan teknis, dan pengelolaan waktu pembelajaran. Secara keseluruhan, video animasi efektif meningkatkan kualitas pembelajaran IPA karena membuat pembelajaran lebih interaktif dan bermakna, meskipun tetap membutuhkan dukungan sarana prasarana dan manajemen pembelajaran yang baik.